Biometric Template Protection using watermarking with hidden password encryption - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (2008)
For quite a few years the biometric recognition techniques have been developed. Here, we briefly review some of the known attacks that can be encountered by a biometric system and some corresponding protection techniques. We explicitly focus on threats designed to extract information about the original biometric data of an individual from the stored data as well as the entire authentication system. In order to address security and privacy concerns, we present a biometric authentication scheme that uses two separate biometric features combined by watermark embedding with hidden password encryption to obtain a non-unique identifier of the personage. Furthermore, to present the performance of the authentication system we provide experimental results. The transformed features and templates trek through insecure communication line like the Internet or intranet in the client-server environment. Our projected technique causes security against attacks and eavesdropping because the original biometric will not be exposed anywhere in the authentication system.